CUSTOMER PREFERENCES ON WEB DESIGN TOWARDS ONLINE FOOD DELIVERY BUSINESS IN BANDAR LAMPUNG, INDONESIA - Linda Septarina; Ridojalani Bin Gefriandi; Rusdee Chemoh (Proceeding International Conference on Information Technology and Business, 2019)
This research conducted is a basic research type with the purpose of acquiring and expanding public knowledge and awareness. The aims of this study are to find out about customer preferences on web design towards online food delivery business in Bandar Lampung, Indonesia. This research is a non-experimental study with variant analysis of data. The main objectives of the research were to analysis of the data that is used in this study consisted of straightforward analysis to look at the factors of web design influenced customer to purchase food using online service through. The number of sample used for a respondent in analysis are randomly 100 chosen people in Lampung from age 18 years old. The respondent will be divided into 50 men and 50 women for sample size selection. The results show that (1) the background and habits of customers using e-service food delivery, (2) the features of web design that greatly influence individual customers and (3) factors of web design is one of the preferences of their decision to buy food through online delivery.Keywords: customer preference, web design, online food